The World of an Irish Merchant Migrant to the Canadas, 1830–43: The Memoir of David Blair Little. Issue 1 (4th May 2019) - Byrne, Angela
ABSTRACT: In May 1830, a previously unknown Ulster merchant left Derry on a ship bound for Canada. In this paper I identify him as David Blair Little. Of a prominent merchant family, Little was educated and well-read, a characteristic of those who left Ireland prior to the 'Great Famine'. This article analyses his self-positioning in relation to other Irish migrants in Canada and the self-differentiating strategies employed in his memoir. The article also disentangles Little's engagement with and borrowings from popular travel accounts of the Canadas and considers their influences on his experiences. His engagement with contemporary literature and popular science illuminates the intellectual life of the middling-sort merchant class in Ulster in the first part of the nineteenth century, an important constituency of the pre-Famine Irish migrant population.